Miranda: The Case, the Man, and the Players - Kamisar, Yale (1984)
On the eve of America's bicentennial, the American Bar Association told its members of a plan to publish a book about the milestone events in 200 years of American legal history, and invited them to vote on the milestones to be included. When the balloting was over, Miranda v. Arizona1 - the high-water mark of the Warren Court's revolution in American criminal procedure2 - had received the fourth highest number of votes.3 I venture to say that if members of the general public had been asked to list the most regrettable or most unfortunate milestones in American legal history, Miranda might have finished even higher in the voting. To many Miranda was the red flag of Warren Court liberalism.' 4 The case plunge[d] the Court into an ocean of abuse and made it one of the leading issues of the 1968 Presidential campaign. S Somebody was bound to write a history of this epochal case, and now, in Miranda: Crime, Law and Politics, Liva Baker has written a book that is massive and exhaustively researched, yet thoughtful and readable. Although this review concentrates on what Baker has to say about Miranda, its ancestry, and its progeny, her book is much more than a book about Miranda the case and Miranda the man and how they fared. It is also a book6 about the Supreme Court, the fights of the accused, the politics of crime, and the social and political history of the 1960's and 1970's. Thus, it is also a book about Earl Warren, Warren Burger, Hugo Black, William Brennan, William Douglas, Abe Fortas, Richard Nixon, George Wallace, John McClellan, James Eastland, and many others. I found it more interesting reading, and much more rewarding, than The Brethren .7 The story of Miranda the case and Miranda the man is told in great detail and told well. For me, however, the least satisfying part of the book is Baker's discussion of the post-Miranda confession cases.8 Although she obviously has learned a great deal about the Supreme Court and about criminal, law and its administration, Baker is not a lawyer. And lawyers, especially law professors, are trained to attack lay persons' analyses of cases the way hounds attack foxes.